Interactional Approach in Improving Students’ Writing Skills as A Strengthening of The Ability of Religious Moderation at State Islamic Institute of Kediri - Wahyuni, Sri (State Institute of Islamic Studies (IAIN) Salatiga, 2021)
This article aims at investigating the effect of interactional approach in improving students’ writing skill as a strengthening of the ability of religious moderation at State Islamic Institute of Kediri. By employing a quasi experimental research design, two groups of students participated in this study. The experimental group was taught by using interactional approach, then the control group was taught by using non interactional approach (self-correction). Direct writing test was used to collect the data, and ANCOVA was used to analyze the data. The finding shows that both approaches can improve students’ writing skill. It can be seen from the improvement of students’ writing mean score from pretest to posttest. The experimental group got 19.18 improvement, and the control group got 16.45 improvement. It seems that the experimental group achieved higher improvement. However, based on the result on ANCOVA calculation, the sig.value obtained was 0.418; it was higher than the significant level (0.05). It means that there was not enough evidence to reject the null hypothesis. There was no significant difference on writing skill between the both groups. Those approaches affect on improvement of students’ writing skill. The implication is that both approaches can be used to improve students’ writing skill. By having good writing skill, they have more chances to do religious proselytizing (dakwah) through producing or writing religious books or written products in English that can be read by many people in the world, and as the form of religious moderation in Islamic higher education.